Knowledge Management System Pada SMA Negeri 2 Bungo - Afianto, Dafit; Assegaff, Setiawan (Jurnal Manajemen Sistem Informasi, 2022)
Technological and scientific progress is increasing and growing rapidly and of course it is a challenge for SMA Negeri 2 Bungo in managing knowledge assets integrated with collaboration, sharing, innovation, and others that will encourage the creation of knowledge management. However, most of the knowledge in Sma Negeri 2 Bungo is currently difficult to store in a system because knowledge is more individual. And therefore the school needs a means that can organize, store, maintain the knowledge in the school. The purpose of this research is to analyze, design and create prototypes related to the application of Knowledge Management System at SMA Negeri 2 Bungo. This study resulted in a prototype of the web-based SMA Negeri 2 Knowledge Management System design that uses PHP programming language and MySQL database containing information about Teacher Data, Announcements, Documents, Discussions, Case Studies, News and several other menus. In addition, the study also used object-based system analysis modeling, namely Use Case Diagram, Class Diagram and Activity Diagram.